A systematic review of the psychological impacts of the Canterbury earthquakes on mental health. (8th April 2019) - Beaglehole, Ben; Mulder, Roger T; Boden, Joseph M; Bell, Caroline J
Abstract: Objective: This systematic review aims to identify and evaluate all studies that measured psychological distress or mental disorder following the Canterbury earthquakes to establish the psychological consequences of the earthquakes on those exposed. A secondary aim is to outline and emphasise key methodological factors in disaster research. Method: Eligible studies were identified following a comprehensive literature search. A quality assessment was undertaken for all included studies. This was followed by methodological and descriptive review. Results: Thirty‐one papers measuring psychological distress or mental disorder following the Canterbury earthquakes were identified. These papers reported outcomes from 20 separate studies of which seven were rated high‐quality, eight were rated medium and five were rated low‐quality. Key methodological findings and outcomes are discussed for each study. Conclusion: The Canterbury earthquakes were associated with widespread but not universal adverse effects on mental health. Disaster research quality is assisted by representative samples, repeated measures, and the use of appropriate controls to allow accurate assessments of psychological consequences to be made. Implications for public health: The presence of widespread adverse effects as a result of the earthquakes suggests broad‐ranging community initiatives are essential to mitigate the negative consequences of disasters.